Phytochemical Investigations and Pharmacological Potential of Organic Extracts of Calotropis gigantea L. Leaves - Adil Jamal; Amina Arif; Shumaila Kiran; Muhammad Naveed Shahid; Md. Belal Hossain (Scientifica)
Calotropis gigantea holds significant therapeutic value in Indian traditional medicine, since it is utilized for the treatment of several diseases. The current study was performed to evaluate the phytochemical profile, antioxidant radical scavenging (DPPH), and hemolytic and antimicrobial activities of organic fractions of C. gigantea leaves. Qualitative and quantitative analysis of phytochemicals, antioxidant components, phenolics, and flavonoids were conducted using organic solvents, including methanol, n-hexane, chloroform, ethyl acetate, n-butanol, and aqueous solutions. The bioactive fractions extracted from the leaf were tested against pathogenic organisms (Escherichia coli, Pseudomonas aeruginosa, Enterococcus faecalis, Aspergillus fumigatus, Aspergillus flavus, and Aspergillus niger) using the agar well diffusion and microdilution broth method. Hemolytic assay was employed to measure erythrocyte damage in response to bioactive fractions. Our study reflected the presence of bioactive constituents (alkaloids, saponins, tannins, flavonoids, terpenoids, cardiac glycosides, and quinones) with abundance of these found in all except n-hexane, ethyl acetate, and aqueous. All extracts contained significant amounts of total phenolics and total flavonoids (μg/mg). DPPH activity measured was maximum in methanolic aqueous followed by n-hexane, ethyl acetate, chloroform, and n-butanol. Methanol, ethyl acetate, and aqueous fractions showed maximum inhibition antibacterial activity in all Gram-positive and Gram-negative strains while antifungal activity tested in all fungal strains against all fractions showed promising inhibition. The results of our investigation indicate that the organic fractions exhibited reduced hemolytic activity, suggesting an enhanced medicinal potential and decreased toxicity of C. gigantea extracts. Based on the current results, it can be inferred that extracts derived from C. gigantea have diverse potential and urge further investigation as a possible reservoir of metabolites, antioxidants, and antibacterial compounds. Nevertheless, it is imperative to utilize an appropriate and standardized solvent extraction methodology in order to recover possible phytochemicals and antioxidants that possess therapeutic properties from C. gigantea.